Wojskowy wymiar reagowania kryzysowego NATO. Doświadczenia i perspektywy .......... 79 - Cieślak, Eugeniusz (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
The article discusses NATO’s lessons learned related to its military engagement in international crisis response efforts after the end of the Cold War. The article includes the discussion of the possible future of NATO’s military involvement in crisis response over the next decade. It analyzes allied concepts and conduct of non-article five crisis response operations using timeframe set by the successive NATO strategic concepts adopted after the end of the Cold War. References to current political declarations and lessons learned from the non-article five crisis response operations served as a departing point for discussion on the future of NATO’s military involvement in crisis response efforts over the next decade.